Evaluating the Effectiveness of Masterweb-Based Learning Management in Enhancing Educational Outcomes - Rohman, Zulfi Endi Dwi; Khamidi, Amrozi; Karwanto, Karwanto; Amalia, Kaniati; Widiyanah, Ima (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to explore and analyze Masterweb-based learning management in an educational context. The main objectives of this research are to: 1) Know the preparation done in Masterweb-based learning management, 2) Examine the integration of Masterweb-based learning management implementation, 3) Evaluate the effectiveness of Masterweb-based learning management, and 4) Assess the impact of the implementation of Masterweb-based learning management on the learning process. Masterweb-based learning management is an innovative approach that utilizes information and communication technology to improve the effectiveness and efficiency of the learning process. With the development of technology, the implementation of this system is expected to overcome various challenges in education, including limited resources, accessibility, and student engagement. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and document analysis. The participants in this study were educators, students and administrators involved in the use of Masterweb. The results show that thorough preparation, effective integration, and continuous evaluation are the keys to successful Masterweb-based learning management. In addition, the implementation of Masterweb has a significant positive impact on improving student engagement and learning outcomes. These include increased learning motivation, easier access to learning resources, and more dynamic interaction between students and teachers. This research provides practical recommendations for further development and implementation of Masterweb-based learning management in various educational institutions. Thus, it is expected that Masterweb can be an effective solution in facing learning challenges in the digital era.